Software quality assurance in a remote client/contractor context - Black, Angus Hugh (Rhodes University, Faculty of Science, Department of Computer Science, 2006)
With the reliance on information technology and the software that this technology utilizes increasing every day, it is of paramount importance that software developed be of an acceptable quality. This quality can be achieved through the utilization of various software engineering standards and guidelines. The question is, to what extent do these standards and guidelines need to be utilized and how are these standards and guidelines implemented? This research focuses on how guidelines developed by standardization bodies and the unified process developed by Rational can be integrated to achieve a suitable process and version control system within the context of a remote client/contractor small team environment.
Keywords: Computer software -- Quality control; Software engineering; Information technology